Which journal should be chosen when submitting a scientific paper? - Cangüven, Önder (Turk J Urol, 2013)
In the field of urology, many new ideas and skills have been developed by surgeons and researchers. To share this knowledge or these skills with colleagues, we should publish our findings in journal articles. This article is an attempt to lucidly convey how to go about submitting a scientific article for publication in an appropriate journal.